Colloidal force probe study of poly(di(ethylene glycol)methylether methacrylate) homopolymer brush layers in aqueous media at different temperatures. (April 2017) - Wassel, Ekram; Wesner, Daniel; Schönherr, Holger
Graphical abstract: Highlights: PDEGMA brushes in water show a monotonic and reversible increase in adherence from 27 °C to 60 °C. The work of adhesion increases sigmoidally with transitions temperatures that agree quantitatively with SPR data. Brushes collapse over a broad temperature range. AFM data explain observed temperature and thickness dependent protein and cell interaction. Abstract: This study reports on the property changes of thermoresponsive layers of end-grafted poly(di(ethylene glycol) methyl methacrylate) (PDEGMA) on gold studied by atomic force microscopy (AFM) in aqueous medium as a function of thickness and temperature. The changes in interaction forces between a hydrophobized colloidal AFM probe and PDEGMA brushes as well as the mechanical properties and swelling of the PDEGMA layers below and above the reported lower critical solution temperature (LCST) of PDEGMA brushes of 32 °C were analyzed. This work corroborates independently acquired data on thermally triggered changes in protein and cell adsorption and release of these brush layers. While the adherence between colloidal probe and PDEGMA showed a monotonic and reversible increase from 27 °C to 60 °C, the work of adhesion increased sigmoidally with increasing temperature. For layer thicknesses from 5 nm to 27 nm, the apparent transition temperature, determined from the corresponding inflection point, varied linearly from 35 °C to 49 °C. These transition temperatures match the transition temperatures determined by the irreversible adsorption of bovine serum albumin via surface plasmon resonance (SPR). Additionally it was concluded from the AFM force-displacement and indentation data that the layers were swollen to three times their dry thickness below the LCST. When the temperature was increased, they collapsed and became progressively more adhesive and stiffer. The interplay of polymer collapse and balanced interactions with the underlying substrate in very thin layers allows one to tune the efficient transition temperature to temperatures above the LCST. Therefore such "smart materials" with unique features can be exploited to fabricate thermoresponsive surfaces with finely tunable collapse temperatures located in the physiological range.